Conductive hearing loss with an intact tympanic membrane due to non-inflammatory causes. Issue 2 (April 2016) - Choi, Jin Hyuk; Lee, Min Young; Park, Ji Hye; Lee, Kyu-Yup; Lee, Sang Heun; Jang, Jeong Hun
Abstract: Objective: We analyzed audiologic and surgical findings in patients with conductive hearing loss (CHL) with an intact tympanic membrane (TM) that was of a non-inflammatory origin. Methods: We reviewed data from patients who underwent exploratory tympanotomy for CHL with intact TM from January 1995 to November 2012. Patients with diseases of non-inflammatory origin were enrolled (69 patients; 79 ears). Patients were categorized into two groups: non-trauma (50 ears) and trauma (29 ears). Demographic data, intraoperative findings, and audiologic results were obtained and analyzed. Results: Overall, the second decade was the most common age of diagnosis in both the non-trauma and trauma groups. Operative findings showed that ossicular dislocation was more prevalent than ossicular fixation; all trauma group subjects had ossicular dislocation. Short columellization or partial ossicular replacement was the most frequently adopted surgical procedures in both groups. Overall, audiologically, air-conduction thresholds (ACs) and air–bone gaps were significantly improved over the short- and long-term period in both groups. However, the non-trauma group had significantly higher preoperative ACs than the trauma group, especially at low frequencies. Conclusion: This study provides clinicians with useful information regarding the clinical characteristics of CHL with intact TM of non-inflammatory origin.